Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5455/medarh.2016.70.119-122
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Ischemic Stroke Patients Compared with National Institutes of Health Stroke Scale

Abstract: Introduction:Scientific guidelines recommend the National Institutes of Health Stroke Scale (NIHSS) for ischemic stroke (IS) assessment. In Clinical Department of Neurology of Split University Hospital Center nurses use the categorization of patients (COP) according to individual needs for health care.Aim:The aim of this study was to demonstrate that there is a positive correlation between the COP and the NIHSS in IS patients.Methods:We analyzed NIHSS scores and COP findings in 325 participants (median age 77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Our analysis of patients with MCI from general clinical data showed that admission NHISS levels were related to MCI occurrence. Currently, the predictive ability of NIHSS values for MCI is widely recognized in clinical practice 15 . A related study 16 reported that for cerebral infarction caused by internal carotid artery system occlusion, the positive predictive value of NIHSS > 9 within 3 h after onset reached 86.4%, and the positive predictive value of NIHSS of 3-7 within 6 h reached 84.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of patients with MCI from general clinical data showed that admission NHISS levels were related to MCI occurrence. Currently, the predictive ability of NIHSS values for MCI is widely recognized in clinical practice 15 . A related study 16 reported that for cerebral infarction caused by internal carotid artery system occlusion, the positive predictive value of NIHSS > 9 within 3 h after onset reached 86.4%, and the positive predictive value of NIHSS of 3-7 within 6 h reached 84.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of patients with MCI from general clinical data showed that admission NHISS levels were related to MCI occurrence. Currently, the predictive ability of NIHSS values for MCI is widely recognized in clinical practice 15 . A related study 16 reported that for cerebral infarction caused by internal carotid artery system occlusion, the positive predictive value of NIHSS > 9 within 3 h after onset reached 86.4%, and the positive predictive value of NIHSS of 3-7 within 6 h reached 84.4%.…”
Section: Discussionmentioning
confidence: 99%